We Need to Talk About Zines: The Case for Collecting Alternative Publications in the Australian Academic University Library. Issue 2 (3rd April 2017) - Wee, Daniel Vincent
Abstract: The paper examines the research potential of zines and the current issues around acquiring these disparate publications for Australian academic libraries. The paper reports a review of the literature and a brief environmental scan in the form of a survey, which suggest that Australian tertiary institutions are undecided or unsure about how and why zines could be a useful research tool in the future. It is argued here that zines are an important component of the cultural fabric of a freethinking, responsive and reflective society. The subversive and at times transgressive nature of zines makes the conscious collecting of these underground texts complex. A review of the current practices of international academic libraries and the survey results undertaken for the purpose of this paper, suggest that Australian academic libraries are behind their overseas colleagues in their consideration of these issues. Zines are important cultural documents that reveal the creativity, values and complexity of unrepresented marginalised youth, among others. The author suggests that, it is imperative that Australian academic libraries actively collect zines to preserve and make available for research, records of hyper-personal, contemporary texts that proffer to the reader an insight into the individual psyche of any given period in time. IMPLICATIONS FOR PRACTICE Creating partnerships and engaging in conversation with zinesters and library staff can assist in the development and creation of a working collection. Collecting zines for its research potential can be speculative; identifying the strengths of your current collection can provide a clear collection development policy for acquiring zines. Educating and demystifying zine culture can assist Australian librarians in determining whether a zine collection is suitable for their institution.